Perspectives of Primary Health Facility Leaders on the Contributions of Clinical Residents During Community Placement in Southwestern Uganda - Peter Chris Kawungezi; Moses Ntaro; Eleanor Turyakira; Andrew Christopher Wesuta; Angela Tushabe; Michael Matte; Ronnie Ndizeye; Fred Mwebembezi; Brian Turigye; Joseph Ngonzi; Edgar Mugema Mulogo (Advances in Medical Education and Practice, 2026)
Background: The Mbarara University of Science and Technology (MUST)’s First Mile Community Health Program (FMCH) has facilitated community placement of clinical residents at Primary Healthcare (PHC) facilities within the MUST catchment area in southwestern Uganda. While community-based training of medical residents is common in sub-Saharan Africa, little is known about how PHC facility leaders perceive its effect on service delivery in Uganda. This assessment aimed to describe the perspectives of PHC facility leaders on the impact of clinical residents’ community placements on PHC services in southwestern Uganda between 2018 and 2023. Methods: From July 2018 to December 2023, 152 clinical residents from ten specialties were placed at PHC facilities in southwestern Uganda. This was a cross-sectional study based on qualitative data-collection techniques. This study focused on MUST clinical residents and PHC facilities in the MUST catchment in southwestern Uganda. We conducted KIIs with 15 health facility leaders until no new ideas emerged. Data were deductively analyzed using WHO’s five strategic directions. Transcripts were transcribed verbatim, repeatedly reviewed, and coded into predefined categories. Interviewers bracketed their own experiences to ensure facility leaders’ perspectives were accurately captured. Results: Of the 15 facility leaders interviewed, most were male and from government HC IVs. Leaders reported that resident placements improved health service delivery through community engagement, enhancing care models through training, mentorship and low-cost innovations, and improving service coordination, including establishing specialized clinics and promoting better use of equipment. Residents also supported advocacy and resource mobilization. However, short placements, inconsistent outreach, staff shortages and lack of specialists limited continuity and sustainability. Conclusion: Facility leaders reported perceived improvement in strengthening PHC services by the clinical residents. Sustaining these gains will require institutionalized partnerships and evaluation of long-term impact. This could contribute to the advancement of primary healthcare services.
Keywords: universal health coverage; health systems strengthening; community placement; service delivery gaps; health professional; medical practice